Comparative proteomic analysis of renal tissue of normotensive and hypertensive rats - Buneeva, O A; Fedchenko, V I; Kaloshina, S A; Zavyalova, M G; Zgoda, V G; Medvedev, A E (Biomeditsinskaia khimiia, 2024)
Comparative proteomic analysis of kidney tissue from normotensive (WKY) and spontaneously hypertensive (SHR) rats revealed quantitative and qualitative changes in renal proteins. The number of renal proteins specific for WKY rats (blood pressure 110-120 mm Hg) was 13-16. There were 20-24 renal proteins specific for SHR (blood pressure 180 mm Hg and more). The total number of identified renal proteins common for both rat strains included 972-975 proteins. A pairwise comparison of all possible (SHR-WKY) variants identified 8 proteins specific only for normotensive (WKY) animals, and 7 proteins specific only for hypertensive ones (SHR). Taking into consideration their biological roles, the lack of some enzyme proteins in hypertensive rats (for example, biliverdin reductase A) reduces the production of molecules exhibiting antihypertensive properties, while the appearance of others (e.g. betaine-homocysteine S-methyltransferase 2, septin 2, etc.) can be interpreted as a compensatory reaction. Renal proteins with altered relative content (with more than 2.5-fold change) accounted for no more than 5% of all identified proteins. Among the proteins with an increased relative content in hypertensive animals, the largest group consisted of proteins involved in the processes of energy generation and carbohydrate metabolism, as well as antioxidant and protective proteins. In the context of the development of hypertension, the identified relative changes can apparently be considered compensatory. Among the proteins with the most pronounced decrease in the relative content in hypertensive rats, the dramatic reduction in acyl-CoA medium-chain synthetase-3 (ACSM3) appears to make an important contribution to the development of renal pathology in these animals.